Export-Led Growth in Chile: Assessing the Role of Export Composition in Productivity Growth - Felicitas Nowak-Lehmann D.; Dierk Herzer; Boriss Siliverstovs (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2005)
This study examines the export-led growth hypothesis using annual time series data from Chile in a production function framework. It addresses the limitations of the existing literature and focuses on the impact of manufactured and primary exports on productivity growth. In order to investigate if and how manufactured and primary exports affect economic growth via increases in productivity, several single-equation and system cointegration techniques are applied. The estimation results can be interpreted as evidence of productivity-enhancing effects of manufactured exports and of productivity-limiting effects of primary exports.
Keywords: F43; C22; O47; 330; Export-led growth; Chile; cointegration